Perlindungan Hukum terhadap Tenaga Kesehatan dalam Pelayanan Kesehatan di Instalasi Bedah Central Rumah Sakit Umum Daerah Kota Mataram (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study examines the importance of legal protection for healthcare workers in medical services, particularly in the Central Surgical Installation of the Regional General Hospital of Mataram City, which involves high medical risks. The background of this research is based on the increasing potential for medical disputes and the vulnerability of healthcare workers to legal claims due to discrepancies between medical outcomes and patient expectations. The objective of this study is to analyze the implementation of legal protection and identify the challenges faced in practice. The research employs a descriptive method with a qualitative approach, utilizing interviews, observations, and documentation studies. The findings indicate that legal protection has been implemented through standard operating procedures, informed consent, and internal hospital policies in accordance with applicable laws and regulations. However, its implementation remains suboptimal due to several constraints, including limited legal awareness among healthcare workers, inadequate legal assistance systems, and increasing public demands. The study implies the need to enhance legal education for healthcare workers and strengthen the role of hospitals in providing effective legal protection to support professional and safe healthcare services.